Similar cardiometabolic effects of high- and moderate-intensity training among apparently healthy inactive adults : A randomized clinical trial (2017)
Background: Metabolic syndrome (MetS) increases the risk of morbidity and mortality from cardiovascular disease, and exercise training is an important factor in the treatment and prevention of the clinical components of MetS. Objective: The aim was to compare the effects of high-intensity interval training and steady-state moderate-intensity training on clinical components of MetS in healthy physically inactive adults. Methods: Twenty adults were randomly allocated to receive either moderate-intensity continuous training [MCT group; 60-80% heart rate reserve (HRR)] or high-intensity interval training (HIT group; 4 × 4 min at 85-95% peak HRR interspersed with 4 min of active rest at 65% peak HRR). We used the revised International Diabetes Federation criteria for MetS. A MetS Z-score was calculated for each individual and each component of the MetS. Results: In intent-to-treat analyses, the changes in MetS Z-score were 1.546 (1.575) in the MCT group and -1.249 (1.629) in the HIT group (between-groups difference, P = 0.001). The average number of cardiometabolic risk factors changed in the MCT group (-0.133, P = 0.040) but not in the HIT group (0.018, P = 0.294), with no difference between groups (P = 0.277). Conclusion: Among apparently healthy physically inactive adults, HIT and MCT offer similar cardiometabolic protection against single MetS risk factors but differ in their effect on average risk factors per subject. Trial registration ClinicalTrials.gov NCT02738385 registered on March 23, 2016 © 2017 The Author(s).